Accessibility and availability of urban green areas within the 15-minute city scope: Lisbon case study - Dias, Cláudia Maria Fialho Aires Fontes (2023)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence